Expression of the ace operon in Escherichia coli is triggered in response to growth rate-dependent flux-signal of ATP. Issue 2 (8th January 2021) - El-Mansi, Mansi; Phue, Je-Nie; Shiloach, Joseph
ABSTRACT: The signal that triggers the expression of the ace operon and, in turn, the transition of central metabolism's architecture from acetogenic to gluconeogenic in Escherichia coli remains elusive despite extensive research both in vivo and in vitro . Here, with the aid of flux analysis together with measurements of the enzymic activity of isocitrate lyase (ICL) and its aceA -messenger ribonucleuc acid (mRNA) transcripts, we provide credible evidence suggesting that the expression of the ace operon in E. coli is triggered in response to growth rate-dependent threshold flux-signal of adenosine triphosphate (ATP). Flux analysis revealed that the shortfall in ATP supply observed as the growth rate (μ ) diminishes from µmax to ≤ 0.43h −1 ( ± 0.02;n4) is partially redressed by up-regulating flux through succinyl CoA synthetase. Unlike glycerol and glucose, pyruvate cannot feed directly into the two glycolytic ATP-generating reactions catalyzed by phosphoglycerokinase and pyruvate kinase. On the other hand, glycerol, which upon its conversion to D-glyceraldehyde, feeds into the phosphorylation and dephosphorylation parts of glycolysis including the substrate-level phosphorylation-ATP generating reactions, thus preventing ATP flux from dropping to the critical threshold signal required to trigger the acetate-diauxic switch until glycerol is fully consumed. The mRNA transcriptional patterns of key gluconeogenic enzymes, namely, ackA, acetate kinase; pta, phosphotransacetylase; acs, acetyl CoA synthetase and aceA, ICL, suggest that the pyruvate phenotype is better equipped than the glycerol phenotype for the switch from acetogenic to gluconeogenic metabolism. Abstract : Expression of the ace operon and, in turn, the transition of central metabolism's architecture from acetogenic to gluconeogenic in Escherichia coli is controlled by the acetate-diauxic switch.